1998
DOI: 10.1093/ajcn/67.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B-6 requirement and status assessment of young women fed a high-protein diet with various levels of vitamin B-6

Abstract: The vitamin B-6 requirement of young women consuming a constant high-protein diet (1.55 g/kg body wt) and the effect of various ratios of vitamin B-6 to protein on this requirement were studied. Eight women were fed a lactoovovegetarian basal diet containing 0.45 mg vitamin B-6 (2.66 micromol as pyridoxine) and 30 micromol carnitine for 92 d. The protocol consisted of successive baseline adjustment (9 d), depletion (27 d), and repletion (two 21-d and then one 14-d) periods. Vitamin B-6 intakes were 1.60, 0.45,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 38 publications
4
40
0
Order By: Relevance
“…Patients had low hemoglobin concentrations in our study; however, vitamin B6 status revealed no effect on hemoglobin concentration. This finding agrees with that of other studies (Ribaya-Mercado et al, 1991;Huang et al, 1998). Patients had low hemoglobin concentrations which may be caused by other factors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Patients had low hemoglobin concentrations in our study; however, vitamin B6 status revealed no effect on hemoglobin concentration. This finding agrees with that of other studies (Ribaya-Mercado et al, 1991;Huang et al, 1998). Patients had low hemoglobin concentrations which may be caused by other factors.…”
Section: Discussionsupporting
confidence: 93%
“…Our critically ill patients not only had an adequate mean 4-PA concentration ( > 3.0 mmol=day; Leklem, 1990), but it also increased proportionately to vitamin B6 intake. In agreement with previous reports (Brown et al, 1975;Leklem, 1990;Huang et al, 1998), urinary 4-PA excretion changed rapidly in response to a change in vitamin B6 intake.…”
Section: Discussionsupporting
confidence: 93%
“…In this review, three of the four papers on intake-status relationship did indeed use more than three indicators to assess vitamin B6 status (Hansen et al 2001, Huang et al 1998, Kretsch et al 1995. In addition, most papers on the association between status indicators of vitamin B6 and certain health outcomes used plasma PLP, which is generally accepted as the best indicator for vitamin B6 status.…”
Section: Intake-statusmentioning
confidence: 92%
“…The depletion-repletion study of Huang et al aimed to examine the vitamin B6 requirement of young women (age range 28-34 years), consuming a constant high-protein diet (1.55 g/kg body weight/day), and the effect of various vitamin B6 intakes on this requirement (Huang et al 1998). This study was at high risk of bias.…”
Section: Depletion-repletion Studiesmentioning
confidence: 99%
See 1 more Smart Citation